Analisis Kepenulisan Surat 1 Petrus: Suatu Tanggapan Terhadap Teori Pseudonymous - Tri Endah Astuti; Betty Latupeirissa (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2021)
The pseudonymous theory in the authorship of 1 Peter is a threat to the authority of 1 Peter. This article aims to respond to the pseudonymous theory. Although it does not represent the view of the evangelical interpreter as a whole, this article attempts to maintain the authority of 1 Peter as an integral part of the Bible. The author presents internal and external evidences that supports the theory that Peter wrote the letter. The author analyzes the material, the writing’s purposes, literature and outline to show internal evidence. The author also presents the ancient documents which have recorded Peter as the author of 1 Peter. The belief in the authority of 1 Peter is to encourage believers to respect every passage in the Bible as the spiritual mind of God. Thus, believers have a solid foundation in thinking, speaking and acting according to God's Word.